Tip-sample deformation in repulsive tapping mode AFM and artifacts in height measurement - Chizhik, SA; Ahn, HS; Shasholko, DI; Suslov, AA (V S V CO. LTD, 2002)
A model of repulsive tapping mode AFM tip-sample deformation is proposed that takes into account the characteristics of the probe (cantilever spring constant, tip curvature radius, tip material rigidity), operation parameters (free oscillation amplitude, set-point parameter) and local elasticity of the sample. Results of calculation of the tip-sample deformation were used to analyse the contribution of these parameters. It was shown that the sample local deformation affects. the results of scanning with hard cantilevers. An algorithm was suggested for elimination of the error from the surface height measurement on heterogeneous materials.